2020
DOI: 10.1007/s12975-020-00805-0
|View full text |Cite
|
Sign up to set email alerts
|

p5 Peptide-Loaded Human Adipose-Derived Mesenchymal Stem Cells Promote Neurological Recovery After Focal Cerebral Ischemia in a Rat Model

Abstract: Adipose-derived mesenchymal stem cells markedly attenuated brain infarct size and improved neurological function in rats. The mechanisms for neuronal cell death have previously been defined in stress states to suggest that an influx of calcium ions into the neurons activates calpain cleavage of p35 into p25 forming a hyperactive complex that induces cell death. Now we report that p5, a 24-residue peptide derived from p35, offers protection to neurons and endothelial cells in vitro. In vivo administration of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…They are isolated from adipose tissue around blood vessels and cultured. They can differentiate into a variety of cells, including bone cells, chondrocytes, and nerve cells [ 18 ]. Compared with other MSCs, ADMSCs are not only easy to obtain but also show multidirectional differentiation potential, and there is no ethical dispute [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are isolated from adipose tissue around blood vessels and cultured. They can differentiate into a variety of cells, including bone cells, chondrocytes, and nerve cells [ 18 ]. Compared with other MSCs, ADMSCs are not only easy to obtain but also show multidirectional differentiation potential, and there is no ethical dispute [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, MSC therapy combined with royal jelly significantly reduced the infarcted volumes, cerebral edema, and serum pro-inflammatory cytokine levels [ 73 ]. The administration of hADSC-loaded P5 peptide to post-stroke rats created conditions that supported drug-loaded hADSC survival, and hADSC loaded with p5 peptide reduced the number of inflammatory cells around the lesion, but did not increase the vascular density around the infarction area [ 74 ]. Gene-modified MSCs can express biologically active gene products, and, therefore, serve as effective vectors for therapeutic gene transfer to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…One important finding of the study is the interest in using EVs from IFNγ pre-activated MSCs to enhance their beneficial effect in the lungs of SSc mice. It has already been shown that MSC priming by hypoxia or genetic modification may enhance their therapeutic properties in other applications [19,20]. Improvement of fibrotic, remodeling and inflammatory markers was observed by comparison with EVs from non-activated MSCs.…”
Section: Discussionmentioning
confidence: 94%